Regional functional synchronizations in dementia with Lewy bodies and Alzheimer's disease. (15th March 2016) - Peraza, Luis R.; Colloby, Sean J.; Deboys, Liam; O'Brien, John T.; Kaiser, Marcus; Taylor, John-Paul
ABSTRACT: Background: Dementia with Lewy bodies (DLB) is a common cause of dementia in the elderly population after Alzheimer's disease (AD), and at early stages differential diagnosis between DLB and AD might be difficult due to their symptomatic overlap, e.g. cognitive and memory impairments. We aimed to investigate functional brain differences between both diseases in patients recently diagnosed. Methods: We investigated regional functional synchronizations using regional homogeneity (ReHo) in patients clinically diagnosed with DLB ( n = 19) and AD ( n = 18), and for comparisons we also included healthy controls (HC, n = 16). Patient groups were matched by age, education, and by the level of cognitive impairment (MMSE p -value = 0.36). Additionally, correlations between ReHo values and clinical scores were investigated. Results: The DLB group showed lower ReHo in sensory-motor cortices and higher ReHo in left middle temporal gyrus when compared with HCs ( p -value < 0.001 uncorrected). The AD group demonstrated lower ReHo in the cerebellum and higher ReHo in the left/right lingual gyri, precuneus cortex, and other occipital and parietal regions ( p -value < 0.001 uncorrected). Conclusions: Our results agree with previous ReHo investigations in Parkinson's disease (PD), suggesting that functional alterations in motor-related regions might be a characteristic of the Lewy body disease spectrum. However, our results in AD contradict previously reported findings for this disease and ReHo, which we speculate are a reflection of compensatory brain responses at early disease stages. ReHo differences between patient groups were at regions related to the default mode and sensory-motor resting state networks which might reflect the aetiological divergences in the underlying disease processes between AD and DLB.